On the effectiveness of electrical characterization of mature Staphylococcal Biofilm - M. Balato; M. Vitelli; C. Petrarca; S. Minucci; M. Aversa; U. Galdiero; M. R. Catania; E. Roscetto; L. Costanzo; A. G. Chiariello; M. Mariconda; G. Balato (Scientific Reports)
Abstract In this paper, the authors describe an experimental study carried out on biological samples consisting of a 96-h mature Methicillin-Resistant-Staphylococcus-Aureus biofilm. The initial objective was to electrically characterize the biofilm using impedance spectroscopy, by scanning a wide range of frequencies [1 Hz ÷ 10 MHz]. Concurrently, confocal microscopy observations, XTT assays, crystal violet staining method and colony-forming unit assay were performed to characterize the biological activity. The experimental investigation unexpectedly demonstrated that the reproducibility of measurement data was significantly affected by the destructive interaction between the electric field and the biofilm. This interaction was found to be strongly dependent on both the amplitude of the field and the exposure time. Moreover, a significative reduction of total biomass of the biofilm was found in a specific frequency range [10 kHz ÷ 100 kHz]. The results suggest several limitations of impedance spectroscopy as a tool for biofilm identification, since the “sample under test” must not be altered during the measurement process. Conversely, they demonstrate the deleterious impact of the electric field on the biofilm, thereby unveiling a potentially efficacious therapeutic paradigm for biofilm treatment. We expect that the open issues highlighted in this paper will be a source of inspiration for further understanding of the mechanism of interaction between the electric field and biofilm, both in terms of treatment and diagnosis.